Design of an Integrated Order Acceptance System in a Palm Oil Machine Component Company: Case Study - Juliza Hidayati; Meilita Tryana Sembiring; Anggi Maharani . S (Journal La Multiapp, 2026)
As demand increases, companies need information systems capable of providing accurate, real-time, and integrated data. However, observations show that ongoing business processes are still carried out manually, such as communicating orders via WhatsApp , manually recording purchase orders (POs), and creating invoices that are not centrally documented. This condition results in various problems, including lost PO documents, duplicate transaction notes, data desynchronization between departments, and delays in order processing. Research This aim for analyzing business processes moment this (as-is) and designing business processes more (to-be) proposals effective and efficient through implementation system Odoo-based Enterprise Resource Planning (ERP). The research method used is descriptive research with data collection techniques in the form of observation and interviews. Analysis was conducted to identify non-value-added activities and system requirements that are appropriate to the company's operational conditions. The results of the study indicate that manual processes cause an average of 11% data accuracy errors per year, reduce operational efficiency, and hinder coordination between departments. The proposed Odoo-based ERP system design is able to integrate sales, purchasing, production, and finance processes so that data flow is automated, consistent, and there is no repetitive recording. This system model has been proven to support increased data accuracy, reduce data duplication, and provide faster and more accurate information for decision-making.